Nazwy komitetów wyborczych w kampanii samorządowej w 2000 roku - Burda, Jadwiga (Słowo. Studia językoznawcze, 2010)
Local elections directly concern local community, however, election campaign differs from parliamentary campaign on account of the size of constituencies. The aim of this soutline was the analysis of names of electoral committees which participated in local election campaign in 2006 and were registered in the National Electoral Office. Majority of these names concerned electoral committees of the voters and are rich research material which is a subject of general typology. Electoral committees are obliged to have a specific name which is an element of candidates’ self-presentation. Furthermore, these names took over the function of election slogans and became the tools in political struggle. Linguistic mechanisms of political persuasion used in the names evoke in voters’ minds certain meaning.